2008
DOI: 10.1086/587698
|View full text |Cite
|
Sign up to set email alerts
|

Type‐Specific Duration of Human Papillomavirus Infection: Implications for Human Papillomavirus Screening and Vaccination

Abstract: There was considerable variation among HPV types with regard to the duration of infection. Coinfection with multiple types contributed to an increased infection duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
136
5
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(177 citation statements)
references
References 39 publications
31
136
5
2
Order By: Relevance
“…The relatively low clearance rate of HPV16 was also reported in earlier studies (Ho et al, 1998;Molano et al, 2003;Richardson et al, 2003). This observation is consistent with other natural history studies of cervical HPV infection (Franco et al, 1999;Moscicki et al, 2006;Trottier et al, 2008). The clearance of hrHPV infections was slower than lrHPV infections which is in accordance with most other investigators (Giuliano et al, 2002;Molano et al, 2003;Richardson et al, 2003;Brown et al, 2005) who have also reported a longer duration of persistence of infection caused by oncogenic rather than non-oncogenic HPV types.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relatively low clearance rate of HPV16 was also reported in earlier studies (Ho et al, 1998;Molano et al, 2003;Richardson et al, 2003). This observation is consistent with other natural history studies of cervical HPV infection (Franco et al, 1999;Moscicki et al, 2006;Trottier et al, 2008). The clearance of hrHPV infections was slower than lrHPV infections which is in accordance with most other investigators (Giuliano et al, 2002;Molano et al, 2003;Richardson et al, 2003;Brown et al, 2005) who have also reported a longer duration of persistence of infection caused by oncogenic rather than non-oncogenic HPV types.…”
Section: Discussionsupporting
confidence: 92%
“…Longer duration of hrHPV persistence in younger women, similar to those enrolled in our study, was also observed by others (Ahdieh et al, 2001;Trottier et al, 2008;). However, some studies have shown that HPV persistence is more common among older women (Castle et al, 2005;Goodman et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Although numerous test kits with high sensitivity and covering a broad spectrum of HPV types are now commercially available, the interpretation of these results is not straight forward. By using these methods, coinfections with multiple HPV types are not only common for normal and low-grade lesions, [21][22][23][24][25] but also found in a notable, although smaller proportion of invasive cancers. [26][27][28][29][30][31] The current understanding favours the notion that only one of the coinfecting types is responsible for cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] ). The coefficient of variation for the duration of infection of HPV-16 reported by Trottier et al 23 is 8.1%, so these values are no longer key uncertainties. What is not clear, as will be discussed below, is that these durations of infection correspond to durations of infectiousness.…”
Section: Overview Of Transmission Modellingmentioning
confidence: 99%
“…The problem arises when attempting to reconcile population-based epidemiological studies of HPV prevalence with a mathematical model: on one hand, it is easiest to use simple classifications in a model (such as 'susceptible', 'infectious' or 'recovered'), but on the other hand, there is no empirical test for dividing the population into these classes. Most mathematical models do not 23 reported a mean HPV-16 prevalence of 2.7% for women aged 18-60. Consider the following calculation, which illustrates how simple interpretations of DNA positivity and immunity cannot be reconciled with epidemiological data.…”
Section: How Do We Interpret Dna Positivity?mentioning
confidence: 99%